Out-of-season spawning of largemouth bass in a controllable recirculating system - Hu, Chen-Hao; Bie, Han-Qing; Lu, Zi-Yi; Ding, Yang; Guan, He-He; Geng, Long-Hui; Ma, Shuai; Hu, Yuan-Xiang; Fan, Qi-Xue; Shen, Zhi-Gang (Frontiers in Physiology, 2023)
Largemouth bass (LMB) production exceeds 0.7 million tons in 2021 and has become one of the most important freshwater aquaculture species in China. The stable and fixed culture cycle led to regular and drastic price fluctuation during the past decade. Strong price fluctuation provides opportunities and challenges for the LMB industry and out-of-season spawning (OSS) and culture will provide technical support for the opportunities. To induce OSS at a low cost, we established a controllable recirculating system that allows precise thermo-photoperiod manipulation. In the system, four experimental groups were assigned, 18NP (18 ℃ overwintering water temperature, natural photoperiod), 18CP (18 ℃ overwintering water temperature, controlled photoperiod), 16CP (16 ℃ overwintering water temperature, controlled photoperiod), and NTNP (natural water temperature and natural photoperiod), to determine the effects of chilling temperature and photoperiod on spawning performance. OSS was observed in all experimental groups without significant differences, except NTNP. The manipulated broodstock can re-spawn three months later in the next spring in advance. Further analysis of the volume percentage of different stages of oocytes provides a base for excellent regression between the volume percentage of the primary growth stage, cortical alveoli stage, vitellogenesis/maturation stage and gonadal development / maturation. Results suggest that the volume percentage of oocytes is a better indicator of gonadal development and maturation than the gonadosomatic index. We also found that LMB prefers palm fiber as the spawning nest compared to the gravel nest. The findings of this work provide important technique guidance for practical OSS of the LMB aquaculture industry and standardization of ovary development and maturation in fish with asynchronous developmental oocytes.